Effects of salt solution on mechanical behaviors of aramid fiber–reinforced polymer (AFRP) sheets and AFRP-to-concrete joints. Issue 12 (December 2016) - Wu, Bo; Zhang, Shuo; Liu, Fentao; Gan, Ting
In this article, the mechanical behaviors of four kinds of specimens (i.e. aramid fiber–reinforced polymer sheets, steel-epoxy adhesive joints, concrete cubes, and aramid fiber–reinforced polymer-to-concrete joints) were evaluated, respectively, after the specimens were immersed in 35 g/L NaCl solution for up to 360 days. Test results show that (a) except for the tensile strength of the aramid fiber–reinforced polymer sheet related to an immersion time of 45 days being 5.0% higher than that of the control sheet, the change in the sheet's tensile strength with the immersion time is not obvious, and the tensile strength of the sheet related to an immersion time of 360 days is almost the same as that of the control sheet; (b) the effect of the salt solution on the modulus of elasticity of the aramid fiber–reinforced polymer sheet is more significant than that on the tensile strength of the sheet, and the elastic modulus of the sheet related to an immersion time of 360 days is 11.1% lower than that of the control sheet; (c) the shear strength of the steel-epoxy adhesive joint experiences severe degradation after being immersed in the salt solution, but the compressive strength of the aged concrete cube is generally larger than that of the control cube; and (d) the maximum local shear stress in the aramid fiber–reinforced polymer-to-concrete joint generally shows a fluctuating increase with the increase in the immersion time, meanwhile the fracture energy of the joint generally increases with the increase in the immersion time, but the failure pattern of the joint with shorter immersion time is different from that with longer immersion time.